Present status of GM crops in India - Singh, R K; Arunachalam, A; Mohapatra, T (Indian Farming, 2020)
While the modern biotechnology hasbeen recognized to have a great potentialfor the promotion of human well-being, adoption of biosafety protocol isnecessary to protect human health andenvironment from the possible adverseeffects of the products of geneticengineering. The debate betweenproponents and opponents of GMtechnology has created major obstaclesin harnessing benefits of the technology.It has now become clear that the publicwill accept the transgenics only whendoubts related with general risks andenvironmental safety are adequatelydispelled. Thus, there is need toorganize public awareness and presentthe benefits of transgenic crops toimprove social attitude for their rationaldeployment. However, ICAR isworking on innovative technologiesincluding transgenic following aboverules/regulations to ensure sustainabilityfor the food, nutrition and healthsecurity of the people and adequatelyprovision for income of the farmersper se.